IMPLEMENTASI KEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN (LP2B) DI KABUPATEN TEGAL (STUDI IMPLEMENTASI PERATURAN DAERAH KABUPATEN TEGAL NOMOR 10 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH KABUPATEN TEGAL TAHUN 2012-2032) - Dian Ayu Wulandari; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The Policy of Perlindungan Lahan Pertanian Pangan Berkelanjutan (LP2B) aims to protect and defend LP2B area to attain food security. 46% of whole area in Tegal Regency has been assigned in Peraturan Daerah as Lahan Pertanian Pangan Berkelanjutan (LP2B). Yet, to date still found unclear data about the extens magnitude of it. This research aims to describe policy implementation of Perlindungan Lahan Pertanian Pangan Berkelanjutan in Tegal Regency based on Peraturan Daerah Kabupaten Tegal Nomor 10 Tahun 2012 about Rencana Tata Ruang Wilayah Kabupaten Tegal Tahun 2012-2032 and to identify supporting also resisting factors. The method we used is descriptive qualitative research. From our research, we find: (i) The agency has not been implementing three strategic listed in Peraturan Daerah due to LP2B policy is still on the process of identification; (ii) The supporting factor of policy implementation is disposition, whereas the resisting factors are communication, resources and bureaucratic structure. There are some recommendations can be given by researcher. First, Making Peraturan Daerah about LP2B policy of other regencies as reference. Second, increasing the number of human resources, intencity of socialization, and coordination among executive agencies. Finally, creating standard operating procedures as soon as possible.